Organizational behavior management : an Islamic approach - Moghimi, Seyed Mohammad (Emerald Publishing Limited, 2019)
Seyed Mohammad Moghimi examines both the everyday and the theoretical insights offered by Islamic sources for managing organizational behavior. He takes a wide-ranging approach to key organizational issues, including organizational communication, organizational leadership, conflict management, and organizational culture and ethics.